Roman topography and latin diction - Heyworth, S (2011)
This article contains five notes on Roman topography. The first three briefly argue (1) that the uia Tecta supposedly to be placed in the Campus Martius has perhaps arisen from corruption of uia Recta; (2) that the temple of Juturna, placed by Ovid near the arches of the Aqua Virgo, could not have stood where Largo Argentina now is, but further north, perhaps in the grounds of Santa Maria in Via; and (3) that the rites of Anna Perenna described by Ovid in Fasti 3 took place near the Mausoleum of Augustus, and not at the recently discovered spring near Piazza Euclide. Note (4) exhibits the evidence for regarding the twin summits of the Capitol and the Arx as the duo luci between which the Asylum was set up, and goes on to suggest that Vergil and Ovid may have used the name Ianiculum to refer to the Arx; (5) demonstrates that in with the name of a hill can refer to any site from the foot up, and builds on this in arguing that the phrase Concordia in Arce refers to a temple constructed where the slope rises from the Forum. © British School at Rome.